MANAGEMENT OF PERSONAL PROTECTIVE EQUIPMENT (PPE) FIRE EXTINGUISHER IN FIRE FIGHTING OFFICIALS IN JEMBER REGENCY - rachmy rosyida (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2023)
In their work, firefighters have a great risk of danger and require PPE in their work. However, the reality in the field of PPE management is still not well implemented. This happens because the facilities provided by the local government of Kabupaten Jember are not maximal and the availability of PPE is not in accordance with the standard. The purpose of this study was to assess the management of personal protective equipment for fire fighters at the Fire Department UPT Jember. This research is descriptive and uses a qualitative approach. This research was conducted at the UPT Pemadam Kebakaran Jember Regency with the informants are the head of potential development of Satpol PP, members of the fire team, and the head of the fire fighting team. The results showed that PPE management is still not running optimally. The PPE identification process is carried out only when a fire incident occurs; some of the PPE they have is still not up to standard; PPE training has never been conducted by the Minister of Home Affairs; PPE storage is still not suitable; does not carry out the PPE disposal and destruction process; PPE guidance is only carried out orally; the implementation of PPE inspections by the Satpol PP is held regularly and suddenly; as well as in the evaluation process carried out informally. Suggestion that can be recommended is that it is necessary to carry out a comprehensive PPE management processing in accordance with the aspects inside.